2005
DOI: 10.1002/cne.20581
|View full text |Cite
|
Sign up to set email alerts
|

Functional organization and hemispheric comparison of primary auditory cortex in the common marmoset (Callithrix jacchus)

Abstract: Hemispheric fine-grain maps of primary auditory cortex (AI) were derived from microelectrode penetrations in the temporal gyrus of the common marmoset (Callithrix jacchus) to 1) compare the functional organization of AI in the marmoset with other mammalian species and 2) compare the right and left AI maps in individual monkeys. Frequency receptive fields (FRFs) were recorded with pure tones. Five FRF parameters were analyzed: characteristic frequency, threshold, sharpness of tuning 10 dB and 40 dB above thresh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 41 publications
3
32
1
Order By: Relevance
“…Studies in anesthetized marmoset and other monkeys have demonstrated Q 10 values Ͻ7 (Table 1, Philibert et al 2005), which is comparable to auditory nerve responses in other studies. In one study, A1 units in owl monkeys trained in an auditory discrimination task were found to exhibit higher Q 10 values near the training frequencies compared with untrained owl monkeys (Recanzone et al 1993).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Studies in anesthetized marmoset and other monkeys have demonstrated Q 10 values Ͻ7 (Table 1, Philibert et al 2005), which is comparable to auditory nerve responses in other studies. In one study, A1 units in owl monkeys trained in an auditory discrimination task were found to exhibit higher Q 10 values near the training frequencies compared with untrained owl monkeys (Recanzone et al 1993).…”
Section: Discussionsupporting
confidence: 80%
“…For marmosets, the bandwidths of auditory thalamus and cortex units (Figs. 2 and 3) are significantly narrower in the awake condition (the present study) than in ketamine-or pentobarbital-anesthetized conditions (Philibert et al 2005). Similarly, in awake macaque monkeys, Recanzone et al (2000) observed finely tuned A1 neurons with bandwidths smaller than or similar to that of the auditory nerve.…”
Section: Discussioncontrasting
confidence: 39%
“…Furthermore, multiunit responses recorded from middle layers of barbiturate-anesthetized marmoset A1 showed predominantly V-shaped FRAs (X. Wang, unpublished data). Another multiunit study of the A1 in anesthetized marmosets (Philibert et al, 2005) also indicates a prevalence of V-shaped FRAs (Q 40 dB Ͻ Q 10 dB , suggesting V-shaped FRAs). Philibert et al (2005) concluded that the functional organization of marmoset A1 is similar to that found in the owl monkey (Recanzone et al, 1999) and the squirrel monkey (Cheung et al, 2001).…”
Section: Discussionmentioning
confidence: 92%
“…Another multiunit study of the A1 in anesthetized marmosets (Philibert et al, 2005) also indicates a prevalence of V-shaped FRAs (Q 40 dB Ͻ Q 10 dB , suggesting V-shaped FRAs). Philibert et al (2005) concluded that the functional organization of marmoset A1 is similar to that found in the owl monkey (Recanzone et al, 1999) and the squirrel monkey (Cheung et al, 2001). These studies suggest that, within the same species, different physiological states may lead to different response properties related to sound level.…”
Section: Discussionmentioning
confidence: 92%
“…Unlike the primary visual cortex, however, CF is the only receptive field feature that progresses in a smooth gradient across the entire spatial extent of an auditory cortical field. The spatial organization of other receptive field parameters, such as spectral bandwidth, binaural interaction type, minimum response latency, and intensity tuning exhibit nonrandom spatial organizations that are independent of CF but often take the form of spatially contiguous "patches" or "modules" (Heil et al 1994;Imig and Adrian 1977;Kelly and Sally 1988;Middlebrooks et al 1980;Nakamoto et al 2004;Philibert et al 2005;Recanzone et al 1999). With the exception of two reports describing a spatial organization for preferred intensity and binaural interaction type , the spatial organization of receptive fields for features other than CF were not described in any auditory cortical field for the rat.…”
Section: Introductionmentioning
confidence: 99%